(3GdQjGVjGJ GdeGdjI OQhS hJWHjbGJ (B/s - (3UajM, UGOb s; (3jbhQ, CMeOs ((3GdLRGFQ(B: s (3OGQ gheI ddWHGYI hGdfTQ hGdJhRjY(B, s, 2019)
(3jJVef GdcJGH WQMG eaUdG HGdTQM GdeHSW eOYeG HJWHjbGJ hJeGQjf eMdhdI dJQSjN Gdage hCNQi eJQhcI dGLJgGO GdeJYde, hdbO Je GYOGOg hab GdHQfGeL GdQSej GdeJYeO ef WQa GddLfI GdHjOGZhLjI GdhWfjI dejOGf GdYdhe GdGbJUGOjI hGdJSjjQ hGdYdhe GdJLGQjI, MjK JfGhd GdahGFO GdHSjWI hGdeQcHI hGdNUhe hGdOaYGJ h GdbQhV, HGdGVGaI Gdi GNJjGQ GdGSJKeGQGJ(B. s
(3GdeQGLY U(B.177s
Keywords: (3GdEbJUGO GdQjGVjs; (3GdQjGVjGJ GdeGdjIs